2008
DOI: 10.1016/j.drugalcdep.2008.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Substance use outcomes 5½ years past baseline for partnership-based, family-school preventive interventions

Abstract: This article reports adolescent substance use outcomes of universal family and school preventive interventions 5½ years past baseline. Participants were 1677 7th grade students from schools (N = 36) randomly assigned to the school-based Life Skills Training plus the Strengthening Families Program: For Parents and Youth 10-14 (LST + SFP 10-14), LST-alone, or a control condition. Selfreports were collected at baseline, 6 months later following the interventions, then yearly through the 12th grade. Measures inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
3
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(120 citation statements)
references
References 58 publications
4
110
3
3
Order By: Relevance
“…Since 2000, Washington State University (WSU) Extension 1 faculty (in collaboration with state and community partners) have promoted the statewide dissemination of SFP 10-14, an internationally recognized evidence-based family skills training program for youth ages 10-14 and their parents (Spoth et al, 2008;Spoth, Redmond, & Lepper, 1999;Spoth, Reyes, Redmond, & Shin, 1999). The goals of SFP 10-14 are to reduce youth problem behaviors by enhancing parenting and youth coping skills.…”
Section: Participants and Proceduresmentioning
confidence: 98%
See 1 more Smart Citation
“…Since 2000, Washington State University (WSU) Extension 1 faculty (in collaboration with state and community partners) have promoted the statewide dissemination of SFP 10-14, an internationally recognized evidence-based family skills training program for youth ages 10-14 and their parents (Spoth et al, 2008;Spoth, Redmond, & Lepper, 1999;Spoth, Reyes, Redmond, & Shin, 1999). The goals of SFP 10-14 are to reduce youth problem behaviors by enhancing parenting and youth coping skills.…”
Section: Participants and Proceduresmentioning
confidence: 98%
“…Despite significant progress in demonstrating the efficacy of health behavior education programs (Botvin & Griffin, 2004;Catalano et al, 2012;Durlak, Weissberg, Dymnicki, Taylor, & Schellinger, 2011;Spoth, Randall, Trudeau, Shin, & Redmond, 2008), the gap between research, practice, and meaningful public health impact remains substantial (Glasgow, Lichtenstein, & Marcus, 2003;Rohrbach, Grana, Sussman, & Valente, 2006;Spoth et al, 2013;Wandersman et al, 2008). Some suggest that this gap occurs because when evidence-based programs (EBPs) are transported into the real world, they are modified to fit local contexts and implemented with less than optimal levels of fidelity (Cohen et al, 2008;Dusenbury, Brannigan, Hansen, Walsh, & Falco, 2005;, and several empirical studies show a positive association between fidelity (i.e., program delivery as designed) and participant outcomes (Breitenstein, Gross, Garvey, Hill, Fogg, & Resnick, 2010b;Byrnes, Miller, Aalborg, Plasencia, & Keagy, 2010;Durlak & DuPre, 2008;Hamre et al, 2010;Hill & Owens, 2013;Pettigrew, Graham, Miller-Day, Hecht, Krieger, & Shin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although raising the minimum legal drinking age from age 18 to 21 has led to reductions in drinking and alcohol-related traffic fatalities (DeJong & Blanchette, 2014;Subbaraman & Kerr, 2013), evidence for the success of other programs targeted at delaying age at initiation is less compelling (Spoth et al, 2008). That there is no precise, shared understanding of what is meant by drinking onset makes direct comparisons across research studies challenging (Rolando et al, 2012).…”
mentioning
confidence: 99%
“…LST has been found to have beneficial effects on shared risk factors for YV and SV, including substance abuse, delinquency/antisocial behavior, and general aggression. Several studies have found that youth who participated in LST had significantly lower rates of substance abuse (Botvin, Griffin, Diaz, & Ifill-Williams, 2001;Spoth, Randall, Trudeau, Shin, & Redmond, 2008), verbal and physical aggression, fighting, and delinquency (Botvin et al, 2006) than comparison youth. Similarly, Positive Action (Beets et al, 2008) is a school-based universal program that emphasizes concepts related to positive behaviors for youth.…”
Section: Universal School-based Programsmentioning
confidence: 99%
“…These partnerships provide opportunities to leverage resources and expertise across states to conduct comprehensive prevention approaches in communities. Rigorous evaluations of PROSPER have demonstrated significant effects on alcohol and drug use, conduct problems, and family outcomes, including connectedness and discipline (Spoth et al, 2008).…”
Section: Prevention Operating Systemsmentioning
confidence: 99%